Novel boron‐containing compound, halogenated boroxine, induces selective cytotoxicity through apoptosis triggering in UT‐7 leukemia. Issue 5 (17th February 2022) - Hadzic, Maida; Pojskic, Lejla; Lojo‐Kadric, Naida; Haveric, Anja; Ramic, Jasmin; Galic, Borivoj; Haveric, Sanin
Abstract: Apoptosis induction is a promising approach in targeting tumor cells. As halogenated boroxine (HB) shows antitumor activity, but its mechanism of action in hematological tumors remains unclear, in this study, we aimed to analyze apoptosis triggering in normal and UT‐7 leukemia cells by HB. Methods for assessing cell viability and cytotoxicity, apoptosis detection, relative expression of 84 apoptosis‐associated genes and BCL‐2, and functional analysis were applied. Pronounced HB activities in inhibition of cell viability, cytotoxicity, and apoptosis induction with measurable differences between tumor and normal cells were found. HB modulated the expression of 21 genes, predominantly downregulated the antiapoptotic genes in leukemia. The functional association revealed HB's impact on inhibition of NF‐κB signaling pathway. BCL‐2 expression decreasing was found only in UT‐7 leukemia. This study identified HB as an apoptosis inducer affecting leukemia but not normal cells considering mechanisms of selective activity that may be a great advantage of HB applications.